2000
DOI: 10.1385/abab:89:2-3:209
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel-Derived Prussian Blue-Silicate Amperometric Glucose Biosensor

Abstract: A new type of inorganic biosensor is introduced. The sensor comprises glucose oxidase enzymes encapsulated in a sol-gel-derived Prussian blue-silicate hybrid network. Glucose is detected by the biocatalytic reduction of oxygen followed by catalytic reduction of hydrogen peroxide by the Prussian blue catalyst. The sol-gel silicate entails a rigid encapsulating matrix, the Prussian blue provides chemical catalysis and charge mediation from the reduction site to the supporting electrode, and the enzyme is respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…A PB-doped silicate film was prepared according to the procedure described by Baharati et al [32]. One mL of MTEOS and 1 mL of methanol were mixed.…”
Section: Pb-doped Silicate Glassy Carbon (Pbdsgc) Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…A PB-doped silicate film was prepared according to the procedure described by Baharati et al [32]. One mL of MTEOS and 1 mL of methanol were mixed.…”
Section: Pb-doped Silicate Glassy Carbon (Pbdsgc) Electrodementioning
confidence: 99%
“…It seems as though the mobility of counter ions controls the rate of the overall redox process. In the case of the PBDSGC electrode it has been suggested that the PB dopant forms a continuum within the inorganic silicate matrix through the interconnected porous structure of the silicate film [32]. It seems that production of non-regular crystalline PB deepen into the insulating silicate matrix is responsible for the decline of the diffusion coefficient of charges in the inorganic redox salt resulting in an increase in DE p and observation of a low current intensity.…”
Section: Studiesmentioning
confidence: 99%
“…Maduraiveeran and Ramaraj 2007a, b;Zhang et al 2015). The silica-based materials have been employed for the modification of the electrode surface among the wide range of materials, and they have attracted considerable attention for chemical and biological catalytic and sensing because of the high reactivity of the surface silane, groups, tunable porosity, high thermal stability, and chemical inertness, enabling the immobilization of different molecules through silane coupling chemistry (Bharathi and Lev 2000;Maduraiveeran and Ramaraj 2007a, b). In the 1980s, the sol-gel chemistry has been utilized for the fabrication of the modified metal such as gold (Au), platinum (Pt), and silver (Ag) interfaces (Gong et al 2014, Jena and Raj 2015, Sampath and Lev 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Operational stability of the PB can be improved by covering its surface with polymer films [2122], by entrapment of the catalysts into sol–gel [2325], and by conductive polymer matrixes [2627]. In [20] we have demonstrated a novel approach for the stabilization of a sensor based on mixed iron-nickel hexacyanoferrates.…”
Section: Introductionmentioning
confidence: 99%